Trace metals, polycyclic aromatic hydrocarbons and polychlorinated biphenyls in the surface sediments from Sanya River, China: Distribution, sources and ecological risk. (1st February 2022) - Cui, Mengke; Xu, Shiliang; Song, Wenqing; Ye, Huibin; Huang, Jialiang; Liu, Binhan; Dong, Bin; Xu, Zuxin
Abstract: The urban inland river ecosystems are now facing comprehensive pollution and governance pressures. Up to now, few works related to the multiple pollution assessment of trace metals, polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) for the urban inland river sediments have been reported in China. Our study investigated the spatial distribution, ecological risk and potential sources of trace metals, PAHs and PCBs in surface sediment collected from 20 sampling sites of Sanya River, Hainan Province, China. The pollution status and potential ecological risk of trace metals were evaluated using the contamination indexes including geoaccumulation index ( I geo ), individual potential ecological risk ( E r i ), potential ecological risk index ( RI ) and pollution load index ( PLI ). Considering the carcinogenicity and toxicity of PAHs and PCBs to human health and the ecological environment, we also analyzed the distributions, sources and adverse biological effects of PAHs and PCBs according to the sediment quality guidelines (SQGs), principal component analysis (PCA) and other source analysis. This study revealed that the surface sediments in Sanya River were extremely slight pollution and showed a very low ecological risk according to I geo, E r i, PLI and RI results for trace metals. Besides, PAHs and PCBs pollution detected may not pose considerable adverse biological effect to ecological environment in a foreseeable period on the basis of comprehensive research results. The overall surface sediments quality of the Sanya River not seem to pose a serious pollution and ecological risk based on the evaluation results of multiple pollution factors. The study provided detailed information on the multiple pollution status and location of surface sediments, one of the key environmental indicators of international tourism cities, in the Sanya River, which would be useful for the water quality improvement of Sanya River and the environmental remediation of the other coastal ecosystems from different regions. Graphical abstract: Image 1 Highlights: Multiple assessment of comprehensive pollution of sediments in Sanya River, China. Distribution and sources of trace metals, PAHs and PCBs were studied. Trace metals, PAHs and PCBs posed a low pollution level and ecological risk. Study gave the vital references for environmental remediation of coastal ecosystems.